Persepsi Dan Strategi Pengelolaan HKM Desa Leboni Kecamatan Pamona Puselemba (Studi Kasus KPHP, Sintuwu Maroso Kabupaten Poso) - Daniel Surya Krisna; Wardah Wardah; Muhardi Muhardi (Mitra Sains, 2019)
The aims of this research are to find out (1) community perception in implementation of social forestry; (2) strategy in social forestry development in Leboni village. This research was a descriptive study. The respondents determined by using purposive sampling technique. The data were analysed by using descriptive analysis and supported by Likert Scale, SWOT Matrix, Quantitative Strategy Planning Matrix. The resul reveal that the perception about quality value indicator is Good (average score 70,0), emosional value indicator is Good (average score 87,0), fungsional value indicator is Very Good (average score 104,0), and generally perception is Good (average of score total 72,8). Five alternative of strategies that could be applied, they are : (1) develop forest farmer group to be business unit; (2) Implement Good Agriculture Practise; (3) making network with private, local government and local custom institution; (4) increasing regency government support for facilitaties and infrastructure; (5) develop local wisdom technique in forest management. The priority strategy is develop forest farmer group to be business unit (Score 5,7041)